Prinsip Non-Diskriminasi dalam Penerapannya pada Peraturan Bank Indonesia tentang Gerbang Pembayaran Nasional - Ananda, Puja Dwi; Ramlan, Ramlan (Faculty of Law, Universitas Jambi, 2020)
This study aims to determine and analyzes the arrangement of non-discrimination principles based on GATs and its implementation in Indonesia from the regulation on the National Payment Gateway. The research method used in this article is a normative legal research by using historical, statutory and case approaches. The research shows that the regulation regarding the principle of non-discrimination is set in the Article II of GATs on the principle of Most Favoured Nation and Article XVII of GATs on the principle of national treatment. The non-discrimination principle states that a country must not be treated differently from other countries that are members of the GATs-WTO as stated in the Schedules of Specific Commitments. Indonesia issues regulations regarding the National Payment Gateway where several articles in the regulation differ from the commitments registered and restrict market access from other countries' services.